2018
DOI: 10.1007/s11538-018-00547-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Model of the Generation and Maintenance of the Shape and Structure of the Multilayered Shoot Apical Meristem of Arabidopsis thaliana

Abstract: One of the central problems in animal and plant developmental biology is deciphering how chemical and mechanical signals interact within a tissue to produce organs of defined size, shape and function. Cell walls in plants impose a unique constraint on cell expansion since cells are under turgor pressure and do not move relative to one another. Cell wall extensibility and constantly changing distribution of stress on the wall are mechanical properties that vary between individual cells and contribute to rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 94 publications
(186 reference statements)
0
33
0
Order By: Relevance
“…(2005); see also Banwarth-Kuhn et al. (2018) in this issue] to the biomechanics. A similar mechanical/regulatory model with breakable springs for the stem cell niche of mouse olfactory receptor neurons was implemented in the Plenum prototype implementation of the dynamical grammars declarative modeling language (Yosiphon 2009).…”
Section: Declarative Modelingmentioning
confidence: 95%
“…(2005); see also Banwarth-Kuhn et al. (2018) in this issue] to the biomechanics. A similar mechanical/regulatory model with breakable springs for the stem cell niche of mouse olfactory receptor neurons was implemented in the Plenum prototype implementation of the dynamical grammars declarative modeling language (Yosiphon 2009).…”
Section: Declarative Modelingmentioning
confidence: 95%
“…The study combining experimental data on the organization of the extracellular matrix and numerical simulations demonstrated that auxin plays an essential role in altering cells' mechanical properties; this process involves the ABP1 and KATANIN 1 proteins (Sassi et al, 2014). Also, the advanced cell-based mathematical model describes the relationship between the concentration of morphogens and the cellular mechanistic properties in the developing apical shoot meristems (Banwarth-Kuhn et al, 2019).…”
Section: Existing Models and Modeling Approachesmentioning
confidence: 99%
“…Thus, the models of plant tissue morphogenesis put at the forefront three biological facts: (i) the dependence on intercellular hormonal signaling, (ii) the importance of the intracellular state and individual cellular characteristics, (iii) the relevance of mechanical stresses in intercellular interactions. Therefore, scRNA-seq technologies, microscopy, imaging techniques, and a range of complementary approaches to measuring cell mechanical properties (Banwarth-Kuhn et al, 2019;Bidhendi and Geitmann, 2019) can provide a complete picture of morphogenetic processes at the cellular level.…”
Section: Existing Models and Modeling Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…A way to bring together these two aspects is to formulate a multi-scale approach, combining several levels of description and allowing them to interact. Several propositions exist and among them, gene-regulated network combined to growth [4,31,58,71,27], averaging approaches through analytical homogenisation [1,35,65,79,82], and the incorporation of a representation of individual cells in a continuous formulation of tissue deformation [5,13,42,48,53,99].…”
Section: Eect Of Dierential Growthmentioning
confidence: 99%